Measures of the functional dependence of random vectors - Tasena S. (2017)
© 2015 Elsevier Inc. All rights reserved. In this work, we define a set of properties that any measure of functional dependence that exists between random vectors should possess. We also construct measures of functional dependence and show that they satisfy the properties mentioned above. Relationships between these measures and previously defined measures of functional dependence between random variables are discussed.